PERAN GURU BAHASA INDONESIA MTsN DI KABUPATEN TRENGGALEK DALAM GERAKAN LITERASI (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
Abstract The literacy movement should be promoted in the education unit. This is due to the low level of literacy activities, especially students. This study aims to determine the role of Indonesian teachers in the literacy movement and the results of the application of the State Islamic Junior High School Literacy Movement in Trenggalek Regency. The method used is qualitative with a descriptive approach. The data source is gained from State Islamic Junior High School Indonesian teachers in Trenggalek Regency. Data collection techniques in this research are observation, interview and documentation. The results showed that the majority of State Islamic Junior High School Indonesian teachers in Trenggalek Regency had played an active role in the literacy movement and had met the criteria as the pioneers of the literacy movement in their respective institutions. As a good example, Indonesian teachers have a very important contribution in the literacy movement. Although in its application there are also challenges that require Indonesian teachers to find solutions to continue developing literacy to be better in its implementation.